2009
DOI: 10.1186/1471-2407-9-365
|View full text |Cite
|
Sign up to set email alerts
|

A 7 gene expression score predicts for radiation response in cancer cervix

Abstract: BackgroundCervical cancer is the most common cancer among Indian women. The current recommendations are to treat the stage IIB, IIIA, IIIB and IVA with radical radiotherapy and weekly cisplatin based chemotherapy. However, Radiotherapy alone can help cure more than 60% of stage IIB and up to 40% of stage IIIB patients.MethodsArchival RNA samples from 15 patients who had achieved complete remission and stayed disease free for more than 36 months (No Evidence of Disease or NED group) and 10 patients who had fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Guo and colleagues suggest that SCCRO5 may be involved in regulating ubiquitination of the proteins involved in DNA-damage repair (20). Consistent with this suggestion, SCCRO5 was found to be part of a panel of seven genes whose expression score predicts radiation response in patients with cervical cancer (47). Further work is required to define the CRLs and protein targets that are dependent on SCCRO5 in the DNA-damage response, cellular activities, and oncogenesis.…”
Section: Discussionmentioning
confidence: 55%
“…Guo and colleagues suggest that SCCRO5 may be involved in regulating ubiquitination of the proteins involved in DNA-damage repair (20). Consistent with this suggestion, SCCRO5 was found to be part of a panel of seven genes whose expression score predicts radiation response in patients with cervical cancer (47). Further work is required to define the CRLs and protein targets that are dependent on SCCRO5 in the DNA-damage response, cellular activities, and oncogenesis.…”
Section: Discussionmentioning
confidence: 55%
“…We have recently shown that, UBE2C is over expressed in cervical cancer (Rajkumar et al 2011) and it is one among the seven-gene signature whose expression pattern could help identify patients to be treated with radiotherapy alone (Rajkumar et al 2009). Our study had shown the SiHa cells expressing the DN-UBE2C to have growth inhibition, relative to the parental and the vector-only transfected SiHa cells (Rajkumar et al 2011).…”
Section: Introductionmentioning
confidence: 77%
“…Triplicate cDNA template samples were amplified and analysed on the ABI Prism 7900HT sequence detection system (Applied Biosystems, Foster City, CA) as described earlier [18]. …”
Section: Methodsmentioning
confidence: 99%